StdTrip: An a priori design process for publishing Linked Data - Salas, Percy E.; Breitman, Karin (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2012)
The Linked Data standard — which is based on the publication of data in the Web as RDF triples — is gaining increasing attention as a way to promote open data interoperability. The publication of data originally stored in relational databases as RDF is known as the RDB-to-RDF approach. The first step in this process requires the mapping of database concepts to RDF vocabularies, used as the base for generating the RDF triples. The selection of such vocabularies is extremely important, because the more standards are reused, the easier it will be to interlink the resulting datasets to other previously published. However, the tools available today, instead of providing adequate support for reuse of standard vocabularies, reinforce the creation of new ones. In our work, we present the StdTrip process, which provides general guidelines for performing the mapping phasis of the RDB-to-RDF approach, promoting the reuse of standard RDF vocabularies.